The Location Premises Of FDI In Poland. The Case Of The Lodz Province - Dorożyński, Tomasz; Świerkocki, Janusz; Urbaniak, Wojciech (Comparative Economic Research. Central and Eastern Europe, 2015)
This paper aims to study the role of various factors in attracting foreign capital to the Province of Lodz. Conclusions are based on the direct questionnaire study conducted among 188 companies with foreign capital which invested in the region. The obtained results indicate that specific Lodz Province (voivodeship) characteristics were of little importance to foreign investors. Both in Poland and in the voivodeship, they were looking for relatively cheap and skilful labour in order to lower their total costs of production. We confirmed that investment incentives were of little importance for the inflow of FDI to the communes and counties of the Province of Lodz. The factors which most discouraged investment in the region were poor transport infrastructure and an uninteresting social infrastructure decisive for the quality of everyday life. Our conclusion is that the inflow of FDI does not eliminate intra-regional disproportions; on the contrary it probably deepens them.